Reasons for decline and measures to promote Nili Ravi buffalo in its breeding tract - M. Gururaj; Krishan Ahuja; F..C. Tuteja; N. Saxena (Revista Científica)
The Food and Agricultural Organization (2000) termed buffalo as an important asset that is undervalued. Currently, there are 208 million buffaloes spread across 77 countries; the majority of the buffaloes are found in India (56.67%), followed by Pakistan (19.28%) and China (13.46%). India is endowed with a rich biodiversity of buffalo germplasm in the form of 20 recognized breeds and several distinct local types. Buffalo husbandry plays a crucial role in rural livelihood, food security, and the agricultural economy in India. Despite significant contribution to milk production, a decline in buffalo population was observed in dairy progressive states like Haryana and Punjab from 2012 to 2019, with a 28% and 22% decline, respectively. The breed-wise data revealed the highest decline in the Nili Ravi buffalo of 65%. The breeding area for Nili-Ravi buffaloes is located in the districts of Amritsar, Firozpur, Tarn Taran, and Gurdaspur in the state of Punjab, India. This decline in the buffalo population is alarming and calls researchers to find reasons for the decline in the Nili Ravi buffalo population and its breeding area, despite the breed performance being at par with any other milk-producing buffalo. In this regard, a study about the reason and extent of the buffalo population decline in the Punjab was carried out. For the study, 180 dairy farmers from Hoshiarpur (31.99%), Taran Tarn (30.76%), and Firozpur (29.62%) districts were selected purposively, where the highest decline in buffalo population was reported. Milk production performance, family pride and docile nature were the main reasons for most (~70%) of the selected farmers to keep Nili Ravi buffalo. However, frequent reproductive problems, less resale value, and off-breed characteristics (white patches) were the primary reasons that forced dairy farmers to shift from Nili Ravi to Murrah buffalo. Although both the Murrah and Nili Ravi breeds have similar productive and reproductive parameters, the Murrah buffalo breed is gaining popularity due to its higher resale value and a lack of associated cultural constraints. Thus, it is suggested to incentivize the Nili Ravi buffalo owners by introducing milk recording programs, improving the supply of superior germplasm for this vital breed, and addressing reproductive problems through awareness campaigns and training programs in convergence with research institutes and state animal husbandry departments, to propagate and conserve the Nili Ravi buffalo breed in the state.